Diseño de un sistema de refrigeración por amoniaco a diferentes temperaturas para una industria de proceso de carne bovina y porcina - Mora-Peraza, Andrés (Instituto Tecnológico de Costa Rica, 2017)
The industrial refrigeration comes to answer the high production cold demand in various application fields, like in the human feed product processing. Carnes Ibiza is a bovine and porcine meet processing company that is looking for an expansion in its productive capacity; for this reason is developed an refrigeration instalation that answers the client’s needs in function of MAG and SENASA sanitary provisions to ensure the Carnes Ibiza’s product quality and safety. This design focuses to mitigate the refrigeration environmental impact, the energy saving and the working safety in its instalations, to give a workable solution in agree to the recommendations given by ASHRAE and IIAR.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Refrigeración industrial; Bovino; Porcino; Seguridad Laboral; Ahorro energético